2015
DOI: 10.1080/03632415.2015.1114926
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Design for Early Detection of Aquatic Invasive Species in Great Lakes Ports

Abstract: We evaluated a pilot aquatic invasive species (AIS) early detection monitoring program in Lake Superior that was designed to detect newly introduced fishes. We established survey protocols for three major ports (Duluth-Superior, Sault Ste. Marie, Thunder Bay) and designed an adaptive cycle for routine evaluation of survey performance. Among the three ports, we found both similarities (species richness) and differences (introduced species detectability, species detection efficiency) with respect to AIS survey p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Similar studies have found that, depending on the body of water, 60 to >200 samples from a single site (i.e., lake or embayment) during a sampling event with an optimized mixture of fisheries gears would be needed to sample most (>90%) of a fish community (Hoffman et al, 2011;Hoffman et al, 2015;Trebitz et al, 2009). We consistently found that the multilocus eDNA metabarcoding assays could detect 50% or 95% of a fish community in fewer samples, as compared to a traditional gear approach.…”
Section: Comparative Measures Of Species Detections Diversity Andsupporting
confidence: 70%
See 3 more Smart Citations
“…Similar studies have found that, depending on the body of water, 60 to >200 samples from a single site (i.e., lake or embayment) during a sampling event with an optimized mixture of fisheries gears would be needed to sample most (>90%) of a fish community (Hoffman et al, 2011;Hoffman et al, 2015;Trebitz et al, 2009). We consistently found that the multilocus eDNA metabarcoding assays could detect 50% or 95% of a fish community in fewer samples, as compared to a traditional gear approach.…”
Section: Comparative Measures Of Species Detections Diversity Andsupporting
confidence: 70%
“…We consistently found that the multilocus eDNA metabarcoding assays could detect 50% or 95% of a fish community in fewer samples, as compared to a traditional gear approach. Similar studies have found that, depending on the body of water, 60 to >200 samples from a single site (i.e., lake or embayment) during a sampling event with an optimized mixture of fisheries gears would be needed to sample most (>90%) of a fish community (Hoffman et al, 2011;Hoffman et al, 2015;Trebitz et al, 2009). Estimates based on F I G U R E 5 Boxplot distributions of the predicted number of samples required for either an eDNA metabarcoding sample (combined 12S and 16S data; dark gray) or traditional gear (light gray) required to sample 50% and 95% of fish species for each inland (n = 8) lake community based on Chao (1987) and first-order jackknife (Burnham and Overton 1978) estimators.…”
Section: Comparative Measures Of Species Detections Diversity Andmentioning
confidence: 79%
See 2 more Smart Citations
“…In the Everglades, drift fence data produced a different picture of non-native relative abundance and occupancy than throw traps, including detecting four non-native species inside WCA that were undetected by throw traps. However, we noted unique detections of non-native fishes by both gear types, indicating that use of multiple methods provides the most effective form of monitoring for biological invasions (Hoffman et al 2016).…”
Section: Discussionmentioning
confidence: 92%